The application of goal setting theory to goal setting interventions in sport: a systematic review - Jeong, Y. H.; Healy, L. C.; McEwan, D. (International Review of Sport and Exercise Psychology, 2023)
Goal setting is one of the most frequently used mental skills in sports, and Goal Setting Theory has been the most prominent theoretical framework upon which goal setting interventions are based. The present study provides a systematic review examining how the tenets of GST have been applied to goal setting interventions in sport. A total of 27 peer-reviewed studies written in English, which implemented goal setting interventions with athletes in a sport-specific, applied (i.e. non-laboratory) context, were examined. The studies included athletes from a range of individual and team sports. The majority of these studies were characterized by their small sample size and strong focus on performance as an outcome measure. Overall, there was inconsistent application of, and mixed evidence supporting theorizing around, the goal characteristics (goal difficulty, specificity, proximity, source, and type) and moderators (ability, commitment, feedback, complexity, and resources) suggested in GST. As the first systematic review of goal setting interventions focused exclusively on athletes in applied sport contexts, the present review provides insight for athletes, coaches, sport psychology practitioners, and researchers. Applied implications and future research directions (e.g. testing individualized goal setting interventions) are provided.